2019
DOI: 10.1177/1049732319877858
|View full text |Cite
|
Sign up to set email alerts
|

Stories of Change: Comparative Time-Framed Experience Telling in Health Promotion Group Discussions

Abstract: In this article, we examine comparative time-framed experience telling: episodes of interaction in health promotion group discussions in which one of the participants tells their experience and, in response, another participant tells their own experiences from separate moments or periods of their life and compares them. In so doing, group members reinforce and encourage the previous speaker’s positive stance or challenge the negative stance toward contextually relevant objects: behavior change and suggested so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Earlier research on interaction dynamics in counseling settings has demonstrated how clients' possibilities are shaped on at least two intertwined levels: The lines of activities put forward in the interaction and how single turns of talk are designed to encourage different kinds of participation (Karhila et al, 2003;Logren et al, 2017aLogren et al, , 2017bLogren et al, , 2019aLogren et al, , 2019bPoskiparta et al, 1998Poskiparta et al, , 2001Tiitinen et al, 2018). Our analysis showed that participation dynamics is also managed at the level of speakership after overlaps.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Earlier research on interaction dynamics in counseling settings has demonstrated how clients' possibilities are shaped on at least two intertwined levels: The lines of activities put forward in the interaction and how single turns of talk are designed to encourage different kinds of participation (Karhila et al, 2003;Logren et al, 2017aLogren et al, , 2017bLogren et al, , 2019aLogren et al, , 2019bPoskiparta et al, 1998Poskiparta et al, , 2001Tiitinen et al, 2018). Our analysis showed that participation dynamics is also managed at the level of speakership after overlaps.…”
Section: Discussionmentioning
confidence: 99%
“…While the small dataset could limit the generalizability of our findings, CA of institutional encounters aims not only at finding generalizable practices but also at describing what kind of practices are possible in a specific context (Peräkylä, 2004). In this research model, generalizability stems from comparing the findings from different contexts, which in our case means earlier findings from the counseling context (Karhila et al, 2003; Logren et al, 2017a, 2017b, 2019a, 2019b; Poskiparta et al, 1998, 2001) and research on VM interaction in different contexts (Ruhleder & Jordan, 2001; Rusk & Pörn, 2019; Seuren et al, 2020). Moreover, by using the concept of participation (Castro et al, 2016; Collins et al, 2007; Halabi et al, 2020) as a basis for theoretical comparison, we have been able to show how delay, which is a general feature of any kind of VM interaction, becomes consequential specifically in counseling contexts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations